(untitled) (Editora Impacto Científico, 2025)
Introduction: In adolescence, a stage marked by intense physiological, psychological, and social transformations, nutrition plays an even more relevant role. In this context, the school emerges as a privileged space for health promotion, since, in addition to its educational function, it directly influences the formation of lifestyle habits. Objective: To report the experience of a conversation circle held with adolescents on healthy eating, highlighting the importance of health education as a strategy for promoting adequate eating habits. Methodology: This is an experience report developed through a conversation circle between Nursing students and local school students, focusing on the theme of healthy eating. Results and Discussion: Based on the observed results, it was noted that the conversation circle enabled adolescents to gain a better understanding of the importance of adopting healthy eating habits in their daily lives. During the activity, students actively participated, sharing examples from their eating routines and showing curiosity about substituting processed foods with more nutritious options. It was also observed that the methodology adopted favored interaction, creating an environment of knowledge exchange between nursing students and school students, which contributed to consolidating the activity as an educational and reflective moment on health promotion. Conclusion: The experience showed that the conversation circle was an effective methodological tool to promote knowledge exchange between nursing students and adolescents, fostering reflections on the importance of healthy eating from an early age.